Space-time in the study of learning trajectories. (2nd January 2021) - Chavez, Jorge
ABSTRACT: Space-time plays a central role in the scientific study of learning trajectories. From a sociocultural perspective, the definition of a set of space-time coordinates enables researchers to identify and examine both the learning activities in which subjects participate and those life events relevant to understanding their learning processes. The present article reports on a systematic literature review that explored the way in which different researchers define space-time coordinates in their work. We identified 24 empirical studies on the subject, analysis of which led us to conclude that the study of learning trajectories requires not only the specific space-time coordinates of those contexts in which a given learning activity takes place, but also the coordinates that people re/co-construct on an experiential or subjective level based on those activities.